2015
DOI: 10.4048/jbc.2015.18.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Trabectedin and Olaparib Combination Regimen in Breast Cancer Cell Lines

Abstract: PurposeTrabectedin induces synthetic lethality in tumor cells carrying defects in homologous recombinant DNA repair. We evaluated the effect of concomitant inhibition of nucleotide-excision repair and poly (ADP-ribose) polymerase (PARP) activity with trabectedin and PARP inhibitors, respectively, and whether the synthetic lethality effect had the potential for a synergistic effect in breast cancer cell lines. Additionally, we investigated if this approach remained effective in BRCA1-positive breast tumor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
(42 reference statements)
0
16
0
1
Order By: Relevance
“…Clearly, trabectedin synergized with both tested PARP1 inhibitors, but we found olaparib was significantly more potent than veliparib. Our result reflects the fact that veliparib is a pure catalytic inhibitor of PARP1 activation, whereas olaparib is a poisoning drug that blocks activated PARP1 enzyme at the site of damage (PARP1-trapping activity) impeding the subsequent recruitment of repairing machinery [11, 52, 55]. We studied the synergism of PARP1 inhibitors and trabectedin in a large set of different tumor cell lines and in in vivo models, demonstrating that PARP1 inhibition improved the antitumor activity of trabectedin in a cell-line dependent intensity, as previously shown in breast cancer and in Ewing’s sarcoma cell lines [44, 55].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Clearly, trabectedin synergized with both tested PARP1 inhibitors, but we found olaparib was significantly more potent than veliparib. Our result reflects the fact that veliparib is a pure catalytic inhibitor of PARP1 activation, whereas olaparib is a poisoning drug that blocks activated PARP1 enzyme at the site of damage (PARP1-trapping activity) impeding the subsequent recruitment of repairing machinery [11, 52, 55]. We studied the synergism of PARP1 inhibitors and trabectedin in a large set of different tumor cell lines and in in vivo models, demonstrating that PARP1 inhibition improved the antitumor activity of trabectedin in a cell-line dependent intensity, as previously shown in breast cancer and in Ewing’s sarcoma cell lines [44, 55].…”
Section: Discussionmentioning
confidence: 94%
“…Our result reflects the fact that veliparib is a pure catalytic inhibitor of PARP1 activation, whereas olaparib is a poisoning drug that blocks activated PARP1 enzyme at the site of damage (PARP1-trapping activity) impeding the subsequent recruitment of repairing machinery [11, 52, 55]. We studied the synergism of PARP1 inhibitors and trabectedin in a large set of different tumor cell lines and in in vivo models, demonstrating that PARP1 inhibition improved the antitumor activity of trabectedin in a cell-line dependent intensity, as previously shown in breast cancer and in Ewing’s sarcoma cell lines [44, 55]. Among the tested BSTS histotypes, Ewing’s sarcoma cells were the most sensitive to the combination, a result that might be explained by the known exquisite sensitivity of the pathognomonic fusion protein EWS/FLI1-expressing cells to both trabectedin and PARP1 inhibition [10, 5659].…”
Section: Discussionmentioning
confidence: 94%
“…Various experimental studies have shown that trabectedin could decrease the recruitment and differentiation of monocytes to TAMs in tumor tissue; suggesting that trabectedin has potential cytotoxic effect against TAMs and can significantly decrease the production of CCL2 and IL‐6 [Germano et al, D'incalci et al, ]. Recently, Ávila‐Arroyo et al [] found in vitro study that combination of trabectedin and olaparib induced G2/M arrest and apoptotic cell death in BRCA1 ‐positive breast tumor cells. Targeting TAMs by some of already approved drugs are listed in Table .…”
Section: Tumor‐associated Macrophagesmentioning
confidence: 99%
“…Preclinical experiments support this concept [4345]. Combination of olaparib and carboplatin has already been assessed in a Phase 1/1b study involving mixed population of patients with BRCA1/2 germ-line mutations, however only 1 out of 42 evaluable patients achieved complete response [46].…”
Section: Introductionmentioning
confidence: 99%